Data on microbiological quality assessment of rural drinking water supplies in Tiran County, Isfahan province, Iran - Khadijeh Jafari; Ali Akbar Mohammadi; Zahra Heidari; Farzaneh Baghal Asghari; Majid Radfard; Mahmood Yousefi; Mahmoud Shams (Data in Brief, 2018)
A lack of access to safe drinking water can lead to adverse health effects such as infection, disease, and undesirable aesthetic problems. The current study focused on the investigation of groundwater quality in Tiran's villages (Isfahan province, Iran). To determine essential microbiological quality, water samples were collected from 46 randomly-selected water wells during a one-year period. The parameters of pH and chlorine were measured on-site. Turbidity was measured at 420 nm using a DR5000 spectrophotometer. Microbiological tests including general thermoforms, Escherichia coli, and thermophiles were carried out according to the National Iranian Standard Method 3759. Data showed that 1.8% of the villages under study had contaminated water resources. The turbidity values for 94.5% of the resources were within recommended limits (<5NTU). In 20.6% of the samples, the residual free chlorine was in the range of 0 to 0.2 mg/L, 8.79% of samples had values greater than the recommended limits, and18.5% had no free residual chlorine. Keywords: Microbiological quality, Drinking water, Turbidity, pH and chlorine, Tiran